Reduction of matrix effects in pesticide residue analysis in food by programmable temperature vaporizer - AHUMADA FORIGUA, Diego Alejandro; GUERRERO DALLOS, Jairo Arturo (Vitae, 2013)
Background: The phenomenon known as the “matrix-induced chromatographic response enhancement” commonly affects the sensibility, precision, and accuracy in pesticide residue analysis. The presence of matrix effects can be given by adsorption and/or thermal decomposition of pesticides on the gas chromatograph injection port. Objective: To reduce the matrix-induced chromatographic response enhancement on pesticide residues analysis in food through the use of several operational modes of programmable temperature vaporizer inlet. Methods: The analyses were carried out in potato (Solanum tuberosum) extracts by gas chromatography with mass spectrometry detector. In this study, four programmable temperature vaporizer splitless modes were investigated: hot, pulsed, cold and solvent vent. Another topic developed in this study has to do with the influence of injection volume, assessed for the matrix effects. Results: The analysis of variance (ANOVA) (α = 0.05) indicates that when the hot splitless is used most compounds are subjected to matrix-induced chromatographic response enhancement. Furthermore, with the pulsed splitless, a decrease in the number of compounds with matrix-induced chromatographic response enhancement was found, approximately 20% compared to the classic hot splitless. Finally, a remarkable decrease in matrix-induced effects was found when cold splitless mode was used, since there was up to 55% reduction in the compounds, relative to traditional hot splitless, that showed statistical differences between responses in matrix-free standards and matrix-matched standards. Conclusions: It was found that the use of conventional hot splitless and pulsed splitless modes caused matrix-induced effects in more than 70% of the studied compounds. In addition, the results indicate that for most compounds there is an inverse relationship between matrix-induced chromatographic response enhancement and the volume of injection.